Pulmonary basaloid squamous cell carcinoma in a dog - Morey-Matamalas, Antonia; de Stefani, Alberta; Corbetta, Davide; Grau-Roma, Llorenc; de Brot, Simone (Elsevier, 2018)
A 9-year-old neutered male crossbred dog with a 4-week history of progressive vestibulocerebellar signs was presented for necropsy examination. Gross examination revealed neoplastic growth in the lungs, thoracic lymph nodes, the left kidney and the cerebellum. Microscopically, the tumour consisted of an infiltrative, densely cellular, basaloid epithelial neoplastic growth with extensive areas of abrupt keratinization. Immunohistochemically, neoplastic cells expressed p63 and partially expressed cytokeratins 5/6. Based on these findings, the tumour was diagnosed as a primary pulmonary basaloid squamous cell carcinoma (BSSC) with metastasis to regional lymph nodes, kidney and brain. As far as the authors are aware, this is the first description of BSCC in an animal species.